New regulatory requirements in revision of ICH Q2(R2) guideline on the validation of analytical procedures - Čarapić, Marija; Vojvodić, Ljiljana; Nikolić, Katarina; Agbaba, Danica (Archives of Pharmacy, 2022)
Guideline ICHQ2(R1) (June 1995) provides general recommendations about performing the validation of standard analytical procedures (HPLC/TLC/GC) used for testing the active substance (AS)/finished product in order to show that the method is suitable for its intended use (ensuring the quality of the medicine). The development of a new guideline ICHQ14 Analytical procedure development is underway, which consequently led to a revision of the guideline ICHQ2 in the R2 version (comments until July 2022). The aim of this paper is to present an overview of new regulatory elements that should be considered during the validation of the analytical procedure. In relation to R1, ICHQ2(R2) provides recommendations for performing/evaluating various validation tests taking into account the specificity of each analytical procedure. Validation principles covering the use of spectroscopic/spectrometric data (e.g. NIR/Raman/NMR/MS) are described, some of which often require multivariate statistical analyzes. Guideline-R1 referred to the most frequently tested specification/process parameters (identification, testing of impurities quantitatively/limit test, assay). R2 describes the methodology for performing validation for testing: elemental impurities (ICP-OES/ICP-MS), genotoxic impurities (LC/MS), dissolution testing (HPLC), particle size determination, core tablet assay by NIR (e.g. in continuous manufacturing), quantitative 1H-NMR for the assay of AS. The validation methodology used in specific tests for biological/biotechnological drugs for biological assay (ELISA, SPR) and impurity testing-quantitative PCR, is also described. If scientifically justified, relevant data from development studies (ICHQ14) can be used instead of validation or the validation process can be abbreviated when an already established platform analytical procedure is used for a new purpose.